IMPLEMENTASI COMMUNITY BASED SOCIAL MARKETING DALAM PROGRAM PENINGKATAN DISABILITY AWARENESS OLEH KOMUNITAS PEDULI INKLUSI NUSANTARA DI BLITAR (The Commercium, 2022)
This study aims to determine the process of implementing a community-based social marketing campaign or Community Based Social Marketing, namely the Disability Awareness Improvement campaign in the Children's Literacy Movement (CLM) program carried out by Komunitas Peduli Inklusi Nusantara (KOPINUS) in Blitar and see the changes felt by the community target.. The Children's Literacy Movement Program (CLM) is a learning assistance program that applies inclusive education and an inclusive environment in its implementation and aims to provide a knowledge and experience related to the world of disability. So that participants can get to know the world of disabilities more deeply and eliminate negative views of people with disabilities. This research uses a qualitative approach with a case study method. Data collection was carried out through observation and interviews with parties involved in the Children's Literacy Movement (CLM) program. The results showed that the Komunitas Peduli Inklusi Nusantara (KOPINUS) has implemented social marketing steps in the concept of community based social marketing. The campaign process will be maximized if every planning is done in more detail. Furthermore, the Children's Literacy Movement (CLM) program received a positive response from the target community and there were differences in the perceptions and behaviors of the participants before joining the Children's Literacy Movement (CLM) program and after participating in the program. Keywords: Disability Awareness, Disability, Inclusive Education, Social Marketing, Community, Community Based Social Marketing